The Effect of Financial Compensation, Work Motivation, and Organizational Culture on Employee Performance - Christina Heti Tri Rahmawati; Maria Hosyeana Margaritis; Ferrynela Purbo Laksono (Sanskara Akuntansi dan Keuangan, 2023)
Human resources are the basic capital in the organizational development process. An organization that can take good care of its employees can be seen from the performance of its employees. If the employee's performance is good then the company manages to manage employees well. The purpose of this study was to determine the effect of financial compensation, work motivation, and organizational culture on employee performance at Stella Duce 2 Yogyakarta Senior High School. This type of research is census research, in which the total population is equal to the number of samples, namely all teaching staff and educational staff at Stella Duce 2 High School Yogyakarta with a total of 45 employees. This study used a data analysis technique, namely multiple linear regression. The results of the study show that 1) financial compensation, work motivation, and organizational culture have a simultaneous effect on employee performance; 2) financial compensation has no significant effect on employee performance; 3) work motivation has no significant effect on employee performance; and 4) organizational culture has a significant effect on employee performance.